Hubungan Kadar Periostin Serum dan Nilai Asthma Control Test pada Pasien Asma di RSUD Dr. Soetomo Surabaya: [Periostin Serum Level and Asthma Control Test in Dr. Soetomo General Hospital Surabaya] - Ni Made Dwita Yaniswari; Muhammad Amin (Jurnal Respirasi, 2018)
Background: Asthma is a heterogenous disease composed of various phenotype. Chronic airway inflammation are fundamental features of asthma. The main treatment of asthma is corticosteroid. The administration of inhaled corticosteroids will reduce the inflammatory process in asthma. Even with adequate inhaled corticosteroid treatment, there are still patients who develop symptoms with lower asthma control test score. Periostin is an extracellular matrix protein as the best single systemic biomarker for assessing tissue eosinophilia, airway remodeling in uncontrolled asthma. The objective of this study was to examine whether serum periostin is correlated with ACT in asthmatic patients. Methods: This research was an observational analytical with cross sectional design conducted in outpatient clinic Dr. Soetomo General Hospital Surabaya for 3 months. In total, we found 40 asthmatic patients who were qualified to the inclusion and exclusion criteria as the research samples.  The questionnaire was filled in to assess the Asthma Control Test and venous blood tests to measure serum periostin levels using Sandwich Enzyme-Linked Immunosorbent Assay (ELISA) method. Results: The mean periostin level profile of the sample was 94.82 ± 19.21 ng/ml and the median was 94.7 ng/ml. The average ACT score was 16.55 ± 2.93 with 85% were uncontrolled asthma. The results of the independent t-test showed serum periostin levels and the level of asthma control based on ACT score in asthmatics patients had a significant correlation (p = 0.024). Conclusion: There is a significant correlation between serum periostin levels and ACT score in asthmatic patients.